Transformation on the Southern Ukrainian Steppe : Letters and Papers of Johann Cornies, Volume II: 1836-1842. - Dyck, Harvey L.; Staples, John R.; Epp, Ingrid I. (Toronto : University of Toronto Press, 2020)
This book documents the Tsarist Mennonite experience through the papers of Johann Cornies (1789-1848), an ambitious and energetic leader of the Mennonite settlement of Molochna. Cornies' papers offer a widow onto both the Mennonite world, and onto the Tsarist state's relationship with minorities of the frontier.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books